Comparison of Pelvic Floor Muscle Strength and Female Sexual Function in Primiparous After Vaginal Delivery with Caesarean Section - Rizqi Rachman, Ary; Lotisna, David; B. Farid, Retno; T. Chalid, Maisuri; Nur Asni, Siti; Andi Mappaware, Nasrudin (International Journal of Psychosocial Rehabilitation, 2020)
A woman's body undergoes many transformations during pregnancy. One of these physical changes affects the pelvic floor as the muscles work harder to maintain the stability of the spine and the pelvis to support the developing fetus. Unfortunately, these normal pelvic floors can lead to permanent pelvic floor damage during childbirth, including various types of pelvic floor dysfunction. Pregnancy also triggers changes in sexual function as well. As pregnancy progresses, women report poorer sexual function. This study aims to analyze the comparison of pelvic floor muscle strength and sexual function in primiparous women after vaginal delivery and caesarean section. Research was conducted from April 2019 to January 2020 with a total of 92 subjects (46 with vaginal delivery and 46 women with caesarean sections). The characteristics of the subjects were obtained. The majority are 20- 25 years old (41.3-60.9%), unemployed (71.7-87%), last education in junior high school (65.2%), normal BMI (56.5-63.1%), baby birth weight 2500-3500g (52.2%-63%). Statistical analysis was performed using Chi Square. The average pelvic floor muscle strength in both groups was 43.92 cmH2O. To compare the strength of pelvic floor muscles and sexual function, they were analyzed using the independent T-test with p = 0.403 and p = 0.213 (p > 0.05). There is no difference in pelvic floor muscle strength and sexual function in primiparous women after vaginal delivery and caesarean section.